Progression through the spliceosome cycle requires Prp38p function for U4/U6 snRNA dissociation. - Xie, J (1998)
The elaborate and energy-intensive spliceosome assembly pathway belies the seemingly simple chemistry of pre-mRNA splicing. Prp38p was previously identified as a protein required in vivo and in vitro for the first pre-mRNA cleavage reaction catalyzed by the spliceosome. Here we show that Prp38p is a unique component of the U4/U6.U5 tri-small nuclear ribonucleoprotein (snRNP) particle and is necessary for an essential step late in spliceosome maturation. Without Prp38p activity spliceosomes form, but arrest in a catalytically impaired state. Functional spliceosomes shed U4 snRNA before 5' splice-site cleavage. In contrast, Prp38p-defective spliceosomes retain U4 snRNA bound to its U6 snRNA base-pairing partner. Prp38p is the first tri-snRNP-specific protein shown to be dispensable for assembly, but required for conformational changes which lead to catalytic activation of the spliceosome.